Interference with the renin-angiotensin system reduces the palatability of 0.3 M NaCl in sodium-deplete rats - Zenatti, A. A. [UNESP]; Pereira, E. D. [UNESP]; Possari, J. [UNESP]; Andrade, C. A.F. [UNESP]; Menani, J. V. [UNESP]; De Luca, L. A. [UNESP] (Elsevier, 2021)
The renin-angiotensin system (RAS) controls hypertonic NaCl intake driven by sodium appetite. Here we investigated whether the antagonism of RAS interferes with hedonic and aversive orofacial motor responses, or palatability, to intraoral infusion of 0.3 M NaCl (hNaCl). Adult rats were depleted of sodium by combined sc injection of furosemide and 24 h removal of ambient sodium. In experiment 1, losartan (AT1 angiotensin II receptor antagonist, intracerebroventricular, 200 μg/μl), produced a three-fold increase in aversive orofacial motor responses to hNaCl. Losartan also suppressed hNaCl intake recorded immediately thereafter. In experiment 2, each animal had repeated recordings of hNaCl intake and orofacial responses to hNaCl distributed for 180 min. Paired recordings of intake and orofacial responses occurred within five successive blocks after the recordings of only orofacial responses when the animals were still sodium deplete (block zero). Captopril (angiotensin converting enzyme blocker, intraperitoneal, 30 mg/kg) inhibited by 75% the hedonic orofacial responses to hNaCl in blocks zero and 1. The hedonic responses to captopril remained the same throughout blocks, but became similar to vehicle from blocks 2 to 5. There was no difference in aversive responses to 0.3 M NaCl between captopril and vehicle. Captopril produced a 70–100% inhibition of hNaCl intake in blocks 1 to 5. The results suggest that angiotensin II acts in the brain increasing the palatability of hypertonic sodium during the consummatory phase of sodium appetite.
Keywords: Affective responses; Dehydration; Gustatory reactivity; Sodium appetite